Comparison of cefixime and amoxicillin plus metronidazole in the treatment of chronic periodontitis - Dukić, Smiljka Dragoslav; Matijević, Stevo; Daković, Dragana; Čutović, Tatjana (Vojnosanitetski pregled, 2017)
Background/Aim. Despite significant advances in current medicine and improvement of overall health education, chronic periodontitis is still a widespread disease. Losing teeth is the most serious complication of this particular illness. The aim of this study was to examine patients with chronic periodontitis in order to evaluate the efficacy of non-surgical therapy and combination of amoxicillin and metronidazole compared with cefixime, which has not been so far used for the treatment of this disease. Methods. Adult patients with chronic periodontitis (n = 90) underwent non-surgical periodontal treatment (zero-day) and then randomly divided into three groups. The group I served as a control, the group II was additionally treated with the combination of amoxicillin and metronidazole (for 7 days), while the group III was treated with cefixime (also for 7 days). To assess the condition of periodontium before and seven days after the therapy, four clinical parameters were used: gingival index (GI), bleeding on probing (BOP), probing depth (PD) and clinical attachment level (CAL). Results. On the day 7 after the beginning of the therapy, we found that all the three groups of patients had statistically significant clinical improvement of three parameters: GI, BOP and PD, but not of the CAL. However, the improvement of PD was only statistically, but not clinically significant. The improvement in the control group of patients on the day 7 was 19% in BOP and 28% in GI; this improvement was statistically highly significant after the addition of amoxicillin plus metronodazole (71% in BOP and 77% in GI) or cefixime (62% in BOP and 82% in GI). Compared to the combination of amoxicillin and metronidazole, cefixim was statistically significantly more effective for GI (p < 0.05), while for the other three clinical parameters their effects were equal. Conclusion. The conjunction of amoxicillin plus metronidazole or cefixime to the causal treatment of patients with chronic periodontitis led to statistically significant improvement in efficacy in relation to GI and BOP parameters, while cefixime was statistically significantly more efficient than the combination of amoxicillin and metronidazole for GI.